Photography and the death of art - Jiménez Moreno, Carlos (Estudios de Filosofía, 1996)
This article sets the consequences that the discovery of photography had on the system of arts and on the frame of theoretical reflection about artistic expressions. In doing it so, the author relates lot hedeath of art the spreading of photography which made evident the idea of the death of art already present in the romantic tradition from Hegel to Schiller. Starting from La muerte del arte y la estética by Dino Formaggio, the author refers to the fact that photography imposes a question on the concept o fart, on the bounds of the system of arts and on the way the artist, the work of an, and the spectator become differentiated.